POST TRAUMATIC STRESS DISORDERS (PTSD) WITH SEVERE DEPRESSION SYMPTOMS WITH ACUTE PSYCHOTIC IN PATIENT WITH HISTORY AS A PEDOPHILE VICTIMS AND DOMESTIC VIOLENCE IN 22 YEARS OLD MAN : A CASE REPORT - Indra Adhiputra, I Ketut Agus (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana)
Post traumatic stress disorders (PTSD) is a disorder that is fairly common in the community. Every event in the life will have its own meaning in later, especially events that occur in childhood. Data in the U.S. showed 60% men and 50% women have a traumatic experience, which develops into PTSD approximately 6.7% of the entire population. While data from the Indonesian National Commission of Women, since 20072010 there has been 91311 cases of sexual violence against women, as well as cases of child sexual abuse reported to reach 250 cases. Presenting symptoms can range from anxiety disorders, depression, until psychotic. The severity of symptoms depends on each self-defense mechanism thus the PTSD symptoms are very diverse.
Keywords: PTSD, sexual and physical violence in children.